KARAKTERISTIK EKOLOGI LOKASI KEBAKARAN HUTAN DAN LAHAN DI DESA RANTAU BAIS KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Nino Vembrianto; Defri Yoza; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Forest is a gift of nature that have the potential and function to maintain the environmental balance. Land and forest fires may degrade the quality of the environment. Rokan Hilir is a regency in Riau region that often happen forest fires. The purpose of this study was to determine the ecological characteristics which include temperature and humidity, rainfall, the volume and the water content of fuel and also the soil at the location of land and forest fires. This research was conducted in Rantau Bais Tanah Putih Rokan Hilir. The method of data collection by means of surveys. Data obtained during the study presented in a table based on the type of activities that can be taken to a conclusion. The results of this study showed that the average value of the temperature and humidity are 32.50C and 64.5%, rainfall is 212.62 mm, and the volume of forest fuel moisture content is 16.8 million m3 and 12.59%, the water content of soil is 279.64%, bulk density was 0.1975, particle density is 1.0975, total pore space is 82.33%, permeability is 169 625 cm/h and C-Organic is 47.66%. Keyword: Forest, Land and Forest Fire, Ecology.